Pendampingan Sertifikasi Halal Self Declare Dalam Program SEHATI Bagi Pelaku UMKM Baratajaya, Gubeng, Kota Surabaya - Aji, Muhyiddin Indra; Mandasari, Virginia (Journal Of Human And Education (JAHE), 2025)
Assistance with halal self-declaration certification is an activity aimed at assisting MSME actors in Baratajaya Village, Surabaya, Gubeng District, Surabaya City. The (SEHATI) program is a free halal certification program organized by the Halal Product Guarantee Organizing Agency (BPJPH) of the Ministry of Religion (KEMENAG). This activity uses several methods namely; analysis, survey, observation, interviews, and the manufacturing process; which involves MSME actors in Baratajaya Village, Gubeng District, Surabaya City. Not all business actors receive assistance, business actors operating in the food and beverage sector such as fried chicken rice, fried rice, rujak, risol, ice dawet, kombucha, and so on receive assistance. This activity is carried out to increase the accessibility of MSMEs, help MSMEs fulfill halal and hygiene requirements, and increase the positive image of halal products. Halal certification can be submitted by fulfilling several requirements; such as NIB, original ID card photo, active e-mail, cellphone number that can be contacted, product photo, product manufacturing materials, and product manufacturing process. The result of this activity is halal certification for the products of the MSMEs assisted so that it can help them compete in a competitive market.